Traditional Cooking Methods Affect Color, Texture and Bioactive Nutrients of Undaria pinnatifida - Shan Jiang (Foods, 2022)
Undaria pinnatifida (U. pinnatifida) is an edible brown seaweed with high health value. The objective of this study was to evaluate the effect of traditional cooking methods (i.e., blanching, steaming, boiling and baking) on the color, texture and bioactive nutrients of U. pinnatifida, so as to screen out the traditional cooking methods more suitable for U. pinnatifida. In this study, methods of blanching and boiling resulted in better reduction in total color difference (0.91 ± 0.58 and 0.79 ± 0.34, respectively) and retention of chlorophyll A (62.99 ± 1.27 µg/g FW and 51.35 ± 1.69 µg/g FW), along with better elevation of fucoxanthin content (increased by 11.05% and 18.32%, respectively). Baking method got the best retention of total phenol content (1.62 ± 0.11 mg GAE/g DW), followed by methods of boiling and blanching (1.51 ± 0.07 mg GAE/g DW and 1.43 ± 0.05 mg GAE/g DW). Among these cooking methods, blanching and boiling seemed to be the more suitable for U. pinnatifida compared to other methods. These results could help to determine the better cooking methods for U. pinnatifida products and provide a scientific and theoretical basis for improving human dietary health.